cho x^2=a^2 + b^2 +ab
a+b=c
CMR: 2x^4=a^4 + b^4 + c^4./
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Ta có;
(5x-2)^2=4(2-x)^2
(5x-2)^2=4(4-4x+x^2)
(5x-2)^2=16-16x+4x^2
(5x-2)^2=(4-2x)^2
5x-2=4-2x
5x+2x=2+4
7x=6
x=6/7
(5x-2)^2=4(2-x)^2
(5x-2)^2=4(4-4x+x^2)
(5x-2)^2=16-16x+4x^2
(5x-2)^2=4^2-16x+(2x)^2
(5x-2)^2=(4-2x)^2
5x-2=4-2x
5x+2x-2-4=0
7x-6=0
7x=6
x=6/7
\(x^2=a^2+b^2+ab\Rightarrow x^4=\left(a^2+b^2+ab\right)^2\)
<=>\(x^4=a^4+b^4+a^2b^2+3a^2b^2+2a^3b+2ab^3\)
<=>\(2x^4=2a^4+2b^4+2a^2b^2+6a^2b^2+4a^3b+4ab^3\)
<=>\(2x^4=a^4+b^4+\left(a^4+4a^3b+6a^2b^2+4ab^3+b^4\right)\)
<=>\(2x^4=a^4+b^4+\left(a+b\right)^4\)
<=>\(2x^4=a^4+b^4+c^4\)(đpcm)